PERAN PENTING INTERAKSI SOSIAL DALAM PEMEROLEHAN BAHASA PERTAMA PADA ANAK USIA DINI - Aliza Arianti, Nur; Nur Izzah, Risma Hanin; Dinda Aulia, Aisyah Salwa; Mintowati (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research focuses on analyzing social interactions that influence language acquisition with the aim of finding out how important the influence of social interactions is on first language acquisition in early childhood. The qualitative descriptive method was used to describe the results of data collection with the research subject, namely a girl named Ratna. The research results explain that first language acquisition can occur through several stages, namely the prelinguistic stage (touching period), one word, two word and many word stages. Apart from that, it is also influenced by social interaction, where social interaction has positive and negative impacts, so the role of parents or educators is very necessary in achieving the right stimulus.